Dose-intensification in early unfavorable Hodgkin's lymphoma: final analysis of the German Hodgkin study group HD14 trial - Tresckow, Bastian von; Meißner, Julia (Journal of clinical oncology, 2012)
Purpose In patients with early unfavorable Hodgkin's lymphoma (HL), combined modality treatment with four cycles of ABVD (adriamycin, bleomycin, vinblastine, and dacarbazine) and 30 Gy involved-field radiotherapy (IFRT) results in long-term tumor control of approximately 80%. We aimed to improve these results using more intensive chemotherapy. Patients and Methods Patients with newly diagnosed early unfavorable HL were randomly assigned to either four cycles of ABVD or an intensified treatment consisting of two cycles of escalated BEACOPP (bleomycin, etoposide, adriamycin, cyclophosphamide, vincristine, procarbazine, and prednisone) followed by two cycles of ABVD (2 + 2). Chemotherapy was followed by 30 Gy IFRT in both arms. The primary end point was freedom from treatment failure (FFTF); secondary end points included progression-free survival (PFS) and treatment-related toxicity. Results With a total of 1,528 qualified patients included, the 2 + 2 regimen demonstrated superior FFTF compared with four cycles of ABVD (P < .001; hazard ratio, 0.44; 95% CI, 0.30 to 0.66), with a difference of 7.2% at 5 years (95% CI, 3.8 to 10.5). The difference in 5-year PFS was 6.2% (95% CI, 3.0% to 9.5%). There was more acute toxicity associated with 2 + 2 than with ABVD, but there were no overall differences in treatment-related mortality or secondary malignancies. Conclusion Intensified chemotherapy with two cycles of BEACOPP escalated followed by two cycles of ABVD followed by IFRT significantly improves tumor control in patients with early unfavorable HL.